Peculiarities of reforms in the field of execution of sentences and probation of Ukraine under martial law - Kolb, O. G.; Pavlyukh, O. A. (Аналітично-порівняльне правознавство, 2025)
This scientific article analyzes the state and level of effectiveness of implementation in criminal-executive activities of modern state programs related to the reform of the specified sphere of social relations. Based on the results of the study, some features of the implementation of relevant measures of a regulatory, organizational-administrative, law enforcement and other nature aimed at qualitatively changing the content of the process of execution – serving sentences under martial law in Ukraine (2022-2025). It is proven that in a situation of constant underfunding of bodies and institutions for the execution of sentences from the State Budget of Ukraine, one of the additional sources in this sense could be income received from the employment of convicts in places of deprivation of liberty, as well as the introduction at the level of a special legislative act of the obligation for the specified subjects of criminal-executive legal relations to work in the process of serving this sentence. It is also stated that in the conditions of mobilization in Ukraine, it is also necessary to significantly change the approaches to staffing the system of the State Penal Service of Ukraine, namely, instead of male personnel who are suitable for military service, it is necessary to involve female personnel, as well as pensioners of this branch of social activity, to work in bodies and institutions. In addition, attention is focused on such a legally significant fact as the absence of proper public control over the process of execution – serving sentences under martial law, which is due to this and the relevant legal restrictions defined in this regard in the Constitution of Ukraine. The above allows us to assert that a qualitative change in the content and direction of reforms in the field of execution of sentences and probation in Ukraine under martial law (2022-2025) is dialectically determined by a number of features of the latter’s influence on the process of execution - serving sentences, as well as the negative trends formed in this regard, the neutralization, blocking, elimination, etc. of which should become the subject of a comprehensive solution at all levels of social activity in our state (legislative, organizational and managerial, control and supervision, doctrinal, etc.).